Analisis Implementasi Teknologi Informasi pada Domain Deliver and Support di PT. RDPI - ,; , (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
Abstract— PT. RDPI is a  freight services company. In addition to transportation services PT. RDPI also has a workshop for making tank, tub, and caroseries. PT. RDPI has implemented IT (Information Technology) in its operations. However, it has not taken measurements to determine the effectiveness of IT implementation. This research was conducted to measure IT implementation using COBIT 4.1 on Deliver and Support (DS) domains including five IT process namely DS1, DS2, DS3, DS5, DS10. The research results obtained maturity level value in domain Deliver an Support is 2,924. The value is categorized as Repeatable but Intuitive Level. This can be interpreted that there has been  same procedure and used in completing the task.